KEBIJAKAN PENANGANAN PENYINTAS HIV/AIDS DI LEMBAGA PEMASYARAKATAN - Rita Komalasari; Nurhayati Nurhayati; Cecep Mustafa (JURNAL KESEHATAN KARTIKA, 2022)
For the first time, this paper provides an insight into HIV/AIDS-related stigma and discrimination in prisons. In doing so, this paper explores the manifestations and sociological explanations of HIV/AIDS-related stigma and discrimination against inmates at the community level and staff members at the institutional level. This paper contributes to the strengthening of HIV prevention and treatment policy. Thus, this paper would beneficial particularly in response to HIV/AIDS in Prison to the Ministry and Prison authorities.